The content and internal control functions in order to create internal control systems of insurance companies - N. .. Zhuravleva; N. .. Kuzovleva (Путеводитель предпринимателя, 2020)
The article focuses on the formation of the internal control system, which contributes to the development of the institute of internal control and is an effective tool to identify and assess risks. Obosnovyvaetsya relationship forming a system of internal controls and to strengthen financial stability of insurance companies. The necessity to ensure an adequate level of reliability of internal control.